Jalinan Komunikasi Bhayangkara Pembina Keamanan dan Ketertiban Masyarakat Dalam Penyelesaian Konflik Sosial di Monjok dan Karang Taliwang Kota Mataram - Wayan Budiarsa; I Wayan Ardhi Wirawan; I Wayan Sutama (Samvada : Jurnal Riset Komunikasi, Media, dan Public Relations, 2026)
This research aims to find the communication bond of Bhayangkara Coach of Public Security and Order (Bhabinkamtibmas) in resolving social conflicts by focusing on a case study of the Monjok and Karang Taliwang conflicts in Mataram City. The method used in this study is a qualitative interpretative case study model. Data were analyzed with the help of Situational Communication Crisis Theory (SCCT), Conflict Theory, and Conflict Resolution Theory. The results of the study formulated three findings. First, the crisis communication network carried out by Bhabinkamtibmas in the Monjok and Karang Taliwang areas took place in an interpersonal, dialogical, humanistic, and continuous manner through a persuasive approach, dialogue, mediation, direct visits, and coordination with community leaders, youth and religious leaders, village governments, and Babinsa, thus creating security stability. Second, the implementation of crisis communication carried out by Bhabinkamtibmas showed a quick, planned, and collaborative response in handling social conflicts, which was realized through identifying the root of the problem, cross-sector coordination, persuasive communication, mediation, deliberation, post-conflict evaluation, and social reconciliation as a strategy for controlling social crises in the community. Third, the crisis communication implemented by the Bhabinkamtibmas (community police officers) has had positive implications for resolving the social conflict between the Monjok and Karang Taliwang communities. This is evidenced by increased trust in the Bhabinkamtibmas, reduced dissemination of provocative information, the creation of a space for constructive dialogue, the growth of values ​​of brotherhood and mutual cooperation, and the establishment of sustainable social reconciliation.